The First Five Year Plan Planning Commission Government of India - Planning Commission, Government of India (Planning Commission, Government of India, 1951)
The Planning Commission was set up in March, 1950 by a Resolution of the Governor India which defined the scope of its work in the following terms : “ The Constitution of India has guaranteed certain Fundamental Rights to the citizens of India and enunciated certain Directive Principles of State Policy, in particular, that the State shall strive to promote the welfare of the people by securing and protecting as effectively as it may a social order in which justice, social, economic and political, shall inform all the institutions of the national life, and shall direct its policy towards securing, among other things
Government of India Planning Commission
Government of India Planning Commission
Keywords: First Five Year Plan